Confused older patients’ experiences of care on a specialist medical and mental health unit compared with standard care wards - Goldberg, Sarah (2012)
There are concerns about cognitively impaired older patients’ experiences of general hospital care. Nottingham University Hospital developed a medical and mental health unit (MMHU) as a demonstration model of best practice dementia care. This thesis describes a controlled clinical trial comparing patients’ experiences of care on the MMHU to standard care wards.